The summary of the Crimea’s history from its origins, under the Abbasids, to Mengli Geray (870/1465). Part 1. - Refat Abduzhemilev (Крымское историческое обозрение)
Recently, a new source on the history of Crimean Khanate and the Golden Horde has received open access for the scientific world. The digitized manuscript is dated 1701 and has the title “Résumé de l’histoire de Crimée” des origines, sous les Abbassides, à Mengli Giray (870/1465) (“The summary of the Crimea’s history” from its origins, under the Abbasids, to Mengli Geray, 870/1465). The location of the manuscript is the University Library of Languages ​​and Civilizations (Bibliothèque universitaire des langues et civilizations). The source is presented in the collection of the Ottoman Turkish manuscripts (Fonds de manuscrits turcs ottomans) under the code MS.TURC.110g.